Cognitive-adaptive Functioning Gap and Mediating Factors that Impact Adaptive Functioning in Chinese Preschool-aged Children with Autism Spectrum Disorder. - Wang, Shi-huan; Zhou, Qing; Chen, Kai-yun; Ceng, Chao-qun; Zhan, Guo-dong; You, Cong; Xing, Yu; Zou, Yuan-yuan; Deng, Hong-zhu (Journal of Autism & Developmental Disorders, 2024)
This study aimed to investigate the gap between adaptive functioning and cognitive functioning, especially verbal and nonverbal intelligence quotient (IQ) in Chinese children with ASD. We systematically explored cognitive functioning, ASD severity, early signs of developmental abnormalities, and socioeconomic factors as mediating factors of adaptive functioning. We enrolled 151 children (age: 2.5?6 years) with ASD and categorized them into one group with IQ ≥ 70 and another with IQ < 70. The two groups were calibrated for age, age at diagnosis, and IQ, and the relationship of adaptive skills with vocabulary acquisition index (VAI) and nonverbal index (NVI) were separately analyzed. Results show that the gap between IQ and adaptive functioning was significant in children with ASD having IQ ≥ 70, with both VAI and NVI showing statistically significant differences (all P < 0.001). VAI correlated positively with scores for overall adaptive skills and specific domains, whereas NVI had no significant correlations with adaptive skill scores. Age of first walking unaided had an independent positive correlation (all P < 0.05) with scores of adaptive skills and specific domains. IQ-adaptive functioning gap is significant in children with ASD having IQ ≥ 70, suggesting that defining "high-functioning autism" merely on the basis of IQ is not appropriate. Verbal IQ and early signs of motor development are specific and possible predictors of adaptive functioning in children with ASD, respectively.